2002
DOI: 10.1067/mtc.2002.119705
|View full text |Cite
|
Sign up to set email alerts
|

The Ross procedure is the procedure of choice for congenital aortic valve disease

Abstract: The Ross procedure for congenital aortic valve disease in children and young adults offers excellent hemodynamics, with the added advantage of real potential for growth. It should be considered the treatment of choice in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 17 publications
4
61
0
1
Order By: Relevance
“…Thirty-nine publications were included: 17 consecutive series with both children and adults [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (nϭ2610; 11 604 patient years); 12 adult patient series 20 -31 (nϭ1749; 7458 patientϭyears); and 10 pediatric patient series [32][33][34][35][36][37][38][39][40][41] (nϭ672; 3374 patient-years). Table 1 provides an overview of the publications obtained by the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-nine publications were included: 17 consecutive series with both children and adults [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (nϭ2610; 11 604 patient years); 12 adult patient series 20 -31 (nϭ1749; 7458 patientϭyears); and 10 pediatric patient series [32][33][34][35][36][37][38][39][40][41] (nϭ672; 3374 patient-years). Table 1 provides an overview of the publications obtained by the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…A proportional increase in the LVOT root diameter (indexed to patient body surface area) was similarly documented in a larger study of 260 patients (136 of whom were Ͻ18 years of age). 32 Other authors have reported progressive dilation of the autograft with differential prevalence, depending on the definition used (generally 4.0 cm or greater), the method used for detection, and the duration of follow-up. 11 Predisposing factors favoring dilation have included anatomic mismatch between the pulmonary and aortic root and a complete aortic root replacement technique without pericardial buttressing of the ascending aorta and annulus.…”
Section: Mortalitymentioning
confidence: 99%
“…Recent literature addressing these issues has generated conflicting reports. 7,14,32 Simon at el 14 documented rapid adaptation of the pulmonary autograft to systemic pressure and normal growth trajectories thereafter, with 95% of patients free from important regurgitation at 4 years. A proportional increase in the LVOT root diameter (indexed to patient body surface area) was similarly documented in a larger study of 260 patients (136 of whom were Ͻ18 years of age).…”
Section: Mortalitymentioning
confidence: 99%
“…Prospective studies in future can suggest homografts as appropriate alternatives in young women. Especially for young women who wants to get pregnant Ross procedure can be a good alternative because its perfect valve hemodynamics and not being thrombogenic [Al-Halees, 2002). However this opertaion is difficult in terms of technical aspect and as the operative mortality is reported as 2-13% in different studies it has to be performed in experienced centres (Rahimtoola, 2003;Schmidtke 2003).…”
Section: Wwwintechopencommentioning
confidence: 99%